Is the fossil rat-kangaroo Palaeopotorous priscus the most basally branching stem macropodiform?. Issue 2 (4th March 2018) - den Boer, Wendy; Kear, Benjamin P.
Abstract : Citation for this article: den Boer, W., and B. P. Kear. 2018. Is the fossil rat-kangaroo Palaeopotorous priscus the most basally branching stem macropodiform? Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2017.1428196.